DAMPAK PERTUMBUHAN EKONOMI DAN PERDAGANGAN INTERNASIONAL TERHADAP KEMISKINAN DI NEGARA BERKEMBANG PADA ERA PANDEMI COVID-19 - Anggraini, Margareta Rina; Fazaalloh, AL Muizzuddin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This research aims to analyze the impact of economic growth and international trade on poverty in developing countries during the Covid-19 pandemic era. This research uses panel data with a random effect model. The period of this research was during the pandemic (2020-2022). The results of this research show that economic growth has a significant impact on reducing poverty in developing countries during the Covid-19 pandemic era. Exports have had a significant impact on reducing poverty in developing countries in the era of the Covid-19 pandemic. Imports do not have a significant impact on poverty in developing countries during the Covid-19 pandemic era